Oral administration of a probiotic Lactobacillus modulates cytokine production and TLR expression improving the immune response against Salmonella enterica serovar Typhimurium infection in mice - Castillo, Natalia Alejandra (2011)
Background: Diarrheal infections caused by Salmonella, are one of the major causes of childhood morbidity and mortality in developing countries. Salmonella causes various diseases that range from mild gastroenteritis to enteric fever, depending on the serovar involved, infective dose, species, age and immune status of the host. Probiotics are proposed as an attractive alternative possibility in the prevention against this pathogen infection. Previously we demonstrated that continuous Lactobacillus casei CRL 431 administration to BALB/c mice before and after challenge with Salmonella enterica serovar Typhimurium (S. Typhimurium) decreased the severity of Salmonella infection. The aim of the present work was to deep into the knowledge about how this probiotic bacterium exerts its effect, by assessing its impact on the expression and secretion of pro-inflammatory (TNFa, IFNg) and anti- inflammatory (IL-10) cytokines in the inductor and effector sites of the gut immune response, and analyzing toll- like receptor (TLR2, TLR4, TLR5 and TLR9) expressions in both healthy and infected mice. Results: Probiotic administration to healthy mice increased the expression of TLR2, TLR4 and TLR9 and improved the production and secretion of TNFa, IFNg and IL-10 in the inductor sites of the gut immune response (Peyer’s patches). Post infection, the continuous probiotic administration, before and after Salmonella challenge, protected the host by modulating the inflammatory response, mainly in the immune effector site of the gut, decreasing TNFa and increasing IFNg, IL-6 and IL-10 production in the lamina propria of the small intestine. Conclusions: The oral administration of L. casei CRL 431 induces variations in the cytokine profile and in the TLRs expression previous and also after the challenge with S. Typhimurium. These changes show some of the immune mechanisms implicated in the protective effect of this probiotic strain against S. Typhimurium, providing an alternative way to reduce the severity of the infection. ￼